2016
DOI: 10.1007/s00439-016-1714-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of kidney structure-related gene variants with type 2 diabetes-attributed end-stage kidney disease in African Americans

Abstract: African Americans (AAs) are at higher risk for developing end-stage kidney disease (ESKD) compared to European Americans. Genome-wide association studies have identified variants associated with diabetic and non-diabetic kidney diseases. Nephropathy loci, including SLC7A9, UMOD, and SHROOM3, have been implicated in the maintenance of normal glomerular and renal tubular structure and function. Herein, 47 genes important in podocyte, glomerular basement membrane, mesangial cell, mesangial matrix, renal tubular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…The rs55703767 SNP is predicted to alter the third amino acid of the canonical triple-helical domain sequence of Glycine (G)-X-Y (where X and Y are often proline (P) and hydroxyproline (Y), respectively) from G-E-D (D=Aspartic) to G-E-Y 63 , potentially impacting the structure of the collagen complex. In addition, a recent study 64 of candidate genes involved in renal structure reported rs34505188 in COL4A3 (not in linkage disequilibrium with rs55703767, r 2 =0.0006) to be associated with ESRD in African Americans with T2D (MAF=2%, OR=1.55, P=5×10 -4 ). Together with the trend towards association we have seen in SUMMIT and the glycemic interaction we have reported here, these findings suggest variation in COL4A3 may be associated with DKD in T2D as well.…”
Section: Discussionmentioning
confidence: 99%
“…The rs55703767 SNP is predicted to alter the third amino acid of the canonical triple-helical domain sequence of Glycine (G)-X-Y (where X and Y are often proline (P) and hydroxyproline (Y), respectively) from G-E-D (D=Aspartic) to G-E-Y 63 , potentially impacting the structure of the collagen complex. In addition, a recent study 64 of candidate genes involved in renal structure reported rs34505188 in COL4A3 (not in linkage disequilibrium with rs55703767, r 2 =0.0006) to be associated with ESRD in African Americans with T2D (MAF=2%, OR=1.55, P=5×10 -4 ). Together with the trend towards association we have seen in SUMMIT and the glycemic interaction we have reported here, these findings suggest variation in COL4A3 may be associated with DKD in T2D as well.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, misfolded proteins will be secreted to the GBM or accumulated in podocytes, disturbing the glomerular permselective barrier properties and activating downstream pathologic pathways (29,30). Recently, a genome-wide association study revealed that a rare variant in African populations, R408H (rs34505188), was associated with type 2 diabetes and -ESKD (31). The frequency of R408H is higher (0.1899) in Han Chinese, on the basis of the 1000 Chinese Genomes data, compared with European (0.069) and African populations (0.028) on the basis of 1000 Genomes Project data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chemicals, drugs, and environmental pollutants can both initiate kidney disease and promote CKD progression [9]. Additionally, gene-gene and gene-environment interactions in AAs contribute to the increased risk of non-diabetic and hypertension-related ESRD [1012]. This review discusses the factors that contribute to the disparities in care of AAs with ESRD and provides recommendations to reduce these disparities.…”
Section: Introductionmentioning
confidence: 99%